2016
DOI: 10.1128/aem.01532-16
|View full text |Cite
|
Sign up to set email alerts
|

Core Genome Multilocus Sequence Typing for Identification of Globally Distributed Clonal Groups and Differentiation of Outbreak Strains of Listeria monocytogenes

Abstract: Many listeriosis outbreaks are caused by a few globally distributed clonal groups, designated clonal complexes or epidemic clones, of Listeria monocytogenes, several of which have been defined by classic multilocus sequence typing (MLST) schemes targeting 6 to 8 housekeeping or virulence genes. We have developed and evaluated core genome MLST (cgMLST) schemes and applied them to isolates from multiple clonal groups, including those associated with 39 listeriosis outbreaks. The cgMLST clusters were congruent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
160
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(168 citation statements)
references
References 51 publications
(102 reference statements)
7
160
0
1
Order By: Relevance
“…The cgMLST approach uses in silico analysis which analyzes more than dozens of housekeeping genes, and is an SNP-based technique, which results in higher discriminatory power and easier standardization. SeqSphere+ bioinformatic software (Ridom GmbH) has been used for cgMLST [5]. In outbreak cases, the specific ST can be determined through wgMLST, cgMLST or rMLST and rare STs can be detected owing to the high discriminatory power of the SNP assay.…”
Section: Species Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The cgMLST approach uses in silico analysis which analyzes more than dozens of housekeeping genes, and is an SNP-based technique, which results in higher discriminatory power and easier standardization. SeqSphere+ bioinformatic software (Ridom GmbH) has been used for cgMLST [5]. In outbreak cases, the specific ST can be determined through wgMLST, cgMLST or rMLST and rare STs can be detected owing to the high discriminatory power of the SNP assay.…”
Section: Species Identificationmentioning
confidence: 99%
“…Resistome analysis, analysis of horizontal transfer of mobile genomic islands, and recombination analysis greatly assist the development of antimicrobial therapeutics, particularly in the context of multidrug-resistant (MDR) strains containing extended-spectrum betalactamases (ESBLs) or carbapenemases [4]. Moreover, transmission tracking is enabled by phylogenetic mapping, and the analysis of clonality or lineage support infection surveillance and control [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The cgMLST methods address this problem by comparing only genes common to a set of bacterial isolates (2). These methods are now mature and have been applied successfully to the analysis of a number of bacterial outbreaks (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).Given the developments in WGS-based strain typing described above, there is much excitement about applying these methods to real-time hospital epidemiology, but the actual cost-benefit equation, the feasibility of achieving results on an actionable time scale, and the technical requirements for implementation in a "real world" clinical microbiology laboratory are difficult to study. In work published in this issue of the Journal of Clinical Microbiology, …”
mentioning
confidence: 99%
“…The cgMLST methods address this problem by comparing only genes common to a set of bacterial isolates (2). These methods are now mature and have been applied successfully to the analysis of a number of bacterial outbreaks (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…Several studies on a variety of bacterial species have already shown that WGS-based typing, based either on single nucleotide variants (SNVs) (Turabelidze et al, 2013;Pightling et al, 2015) or on gene-by-gene allelic profiling of core genome genes, frequently named core genome MLST (cgMLST) or MLST + (Laing et al, 2010;Mellmann et al, 2011;Köser et al, 2012;Maiden et al, 2013;Antwerpen et al, 2015;de Been et al, 2015;Moran-Gilad et al, 2015;Chaudhari et al, 2016;Moura et al, 2016), currently represents the ultimate diagnostic typing tool that have been successfully applied for outbreak investigations (Figure 9) (den Bakker et al, 2014;Schmid et al, 2014;Ruppitsch et al, 2015b; Lepuschitz, 2015). Molecular typing of bacteria for epidemiological surveillance and outbreak investigation Burckhardt et al, 2016;Chen et al, 2016;Jackson et al, 2016). Backward compatibility of NGS to former methods can be maintained by the extraction of the respective information from NGS data (Hyden et al, 2016).…”
mentioning
confidence: 99%